Kunst und Sport Malerei, Graphik und Plastik des 20. Jahrhunderts in Baden-Württemberg - Reinhardt, Brigitte 1944- (Ed. Cantz, 1986)
A catalog based on the exhibition "Kunst und Sport" held August 9 through September 14, 1986 at the Galerie der Stadt Stuttgart.
Keywords: Geschichte 1900-2000; Geschichte; Art, German -- Germany -- Baden-Württemberg -- Exhibitions; Art, Modern -- 20th century -- Germany -- Baden-Württemberg -- Exhibitions; Sports in art; Sports in art -- Exhibitions; Sports -- History -- Exhibitions; Sport; Kunst; Deutschland; Baden-Württemberg; Ausstellungskatalog -- 1986 -- Stuttgart